Effectiveness and Safety of Non–Vitamin K Antagonist Oral Anticoagulant and Warfarin in Cirrhotic Patients With Nonvalvular Atrial Fibrillation - Lee, Hsin‐Fu (J Am Heart Assoc, 2019)
BACKGROUND: Liver cirrhotic patients with nonvalvular atrial fibrillation have been excluded from randomized clinical studies regarding oral anticoagulants for stroke prevention. Whether non–vitamin K antagonist oral anticoagulants (NOACs) are superior to warfarin for these patients remains unclear. METHODS AND RESULTS: This nationwide retrospective cohort study, with data collected from the Taiwan National Health Insurance Research Database, enrolled 2428 liver cirrhotic patients with nonvalvular atrial fibrillation taking apixaban (n=171), dabigatran (n=535), rivaroxaban (n=732), or warfarin (n=990) from June 1, 2012, to December 31, 2016. We used propensity score–based stabilized weights to balance covariates across study groups. Patients were followed until the occurrence of an event or the end date of study. The NOAC group (n=1438) showed risk of ischemic stroke/systemic embolism and intracranial hemorrhage comparable to that of the warfarin group (n=990) after adjustment. The NOAC group showed significantly lower risk of gastrointestinal bleeding (hazard ratio: 0.51 [95% CI, 0.32–0.79]; P=0.0030) and all major bleeding (hazard ratio: 0.51 [95% CI, 0.32–0.74]; P=0.0003) compared with warfarin group. Overall, 90% (n=1290) of patients were taking a low‐dose NOAC (apixaban 2.5 mg twice daily, rivaroxaban 10–15 mg daily, or dabigatran 110 mg twice daily). The subgroup analysis indicated that both dabigatran and rivaroxaban showed lower risk of all major bleeding than warfarin. The advantage of lower gastrointestinal and all major bleeding with NOACs over warfarin is contributed by those subgroups with either nonalcoholic or nonadvanced liver cirrhosis. CONCLUSIONS: NOACs have a risk of thromboembolism comparable to that of warfarin and a lower risk of major bleeding among liver cirrhotic Asian patients with nonvalvular atrial fibrillation. Consequently, thromboprophylaxis with low‐dose NOACs may be considered for such patients.